2014
DOI: 10.1097/moo.0000000000000067
|View full text |Cite
|
Sign up to set email alerts
|

Update on mandibular distraction osteogenesis

Abstract: Rates of activation can be accelerated with the addition of stem cells and growth factors to distraction sites, as could time to full consolidation. The addition of mesenchymal stem cells and deferoxamine and the use of low-intensity ultrasound during distraction are three of the most promising approaches reported in recent studies with potential for future translation from animal models. Computer-assisted presurgical planning offers added accuracy and potential time savings. Newer distraction devices using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Recently, it has been shown that stromal cell-derived factor-1 facilitates migration of endogenous MSCs in vitro and in vivo , which makes it a potential target that can be manipulated to upregulate an ongoing endogenous process. Moreover, the use of BMP and FGF along with transplantation of MSCs dramatically improves outcomes in osteogenic distraction compared to the cell transplant alone (Earley & Butts, 2014). …”
Section: Stem Cells In Mandible and Tongue Regenerationmentioning
confidence: 99%
“…Recently, it has been shown that stromal cell-derived factor-1 facilitates migration of endogenous MSCs in vitro and in vivo , which makes it a potential target that can be manipulated to upregulate an ongoing endogenous process. Moreover, the use of BMP and FGF along with transplantation of MSCs dramatically improves outcomes in osteogenic distraction compared to the cell transplant alone (Earley & Butts, 2014). …”
Section: Stem Cells In Mandible and Tongue Regenerationmentioning
confidence: 99%
“…Distraction osteogenesis is a lengthy and risky procedure that can result in post-operative non-union, infection, bleeding and device failure. Any of these complications ultimately prolong the period of treatment [25].…”
Section: Introductionmentioning
confidence: 99%
“…Mandibular distraction osteogenesis (MDO) and alveolar distraction osteogenesis are among many surgical techniques that have been studied using Göttingen Minipigs [23, 2632]. Even more important has been the search for methodologies to enhance the process of distraction by accelerating the rates of activation and bone healing or to promote the osseointegration of bony implants utilizing novel biomaterials, implant coatings, growth factors such as morphogenetic proteins, angiogenic factors and autologous mesenchymal stem cells [22, 23, 25, 33, 34].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Thus, the pre-operational preparation of surgery guides is very important. [5] Most of the surgery guides used for mandibular distraction osteogenesis are hand-made, and so may carry disadvantages like poor dimensional accuracy, easy deformation, and long processing time, that do not meet the requirements of clinical use. Three-dimensional (3D) printing has several advantages for this purpose, including digitalization, flexibility, and customization during the fabrication process, all of which may improve dimensional accuracy and reduce complications.…”
Section: Introductionmentioning
confidence: 99%